The Effectiveness of Law Enforcement in Counteracting Hoaxes in the Digital Age between Regulation and Literacy - Depri Udin; Rinaldi Goklas; Crisdo (Yayasan Cinta Negara, 2025)
The phenomenon of spreading hoaxes in the digital era has had a serious impact on society and social stability in Indonesia. This research aims to analyze the effectiveness of law enforcement in counteracting hoaxes, as well as examine the role of digital literacy as a complement to existing regulations. The approach used is normative qualitative with data collection techniques through literature study, expert interviews, and legal document analysis. The research findings show that multiple interpretations of articles in the Electronic Information and Transaction Law (ITE Law) and the weak capacity of law enforcement officers are the main obstacles in prosecuting hoaxes. In addition, the low level of digital literacy and limited access to quality information exacerbate the spread of disinformation. This research recommends a synergy between strict law enforcement and sustainable strengthening of digital literacy through collaboration between the government, educational institutions and communities. With this integrative approach, it is hoped that efforts to counter hoaxes can be more effective in maintaining information security and social stability in the digital era